A comparison of the physical demands associated with various right-angle direct-current power tools. (October 2021) - Cort, J.; Eaton, L.; Smets, M.; Stephens, A.; Malone, G.; Porto, R.
Abstract: This work examined the physical demands associated with 4 commercially available direct current right-angle power tools along with their computer controlled fastening strategies. Physical demands were measured via an external instrumented handle that could also control the trigger of each tool. Data revealed that forces recorded by the external handle for each of the 4 tools differed. Independent of Joint-Hardness and Target Torque the Atlas Copco TurboTight® and Cleco Low Torque Reaction fastening strategies, both using a rapid spindle-head rotation strategy, produced the lowest peak and impulse force, respectfully, when compared to the 2 tools that were designed to fasten with a longer duration. This work has shown that short duration fastening strategies provide an ergonomics benefit to the users as it requires less force to operate, such force reduction in previous research has been linked to reduced handle displacement and lower muscle effort. Highlights: Musculoskeletal injuries are commonly associated with power-tool operation. Physical demand comparison between various commercially available right-angle power tools programmable tightening strategies is warranted to objectively understand their ergonomic benefit. TurboTight® strategy was proven to have the greatest reduction in reaction force. Fast spindle fastening strategies drastically reduces the force experienced at the handle during right-angle power tool operation.